Trace form associated to cyclic number fields of ramified odd prime degree - Araujo, Robson R.; Chagas, Ana C. M. M.; Andrade, Antonio A. [UNESP]; Nóbrega Neto, Trajano P. [UNESP] (World Scientific Publishing, 2019)
In this work, we computate the trace form Tr k/Q (x2) associated to a cyclic number field of odd prime degree p, where p ramified in and x belongs to the ring of integers of . Furthermore, we use this trace form to calculate the expression of the center density of algebraic lattices constructed via the Minkowski embedding from some ideals in the ring of integers of .
Keywords: algebraic lattices; cyclic number fields; Trace form